Antimicrobial activities of marine fungi from Malaysia - Zainuddin, N.; Alias, S.A.; Lee, C.W.; Ebel, R.; Othman, N.A.; Mukhtar, M.R.; Awang, K. (Walter De Gruyter & Co, 2010)
In a systematic screening effort, extracts of marine fungi from Malaysia were investigated for antimicrobial activity and potentially active secondary metabolites. In preliminary experiments, the plug assay method was employed to screen 152 strains for antimicrobial activity. Of these, 82 exhibited biological activity, with most of the active strains (90.2%) having antibacterial activity, mainly towards Gram-positive bacteria, while only 9.6% had antifungal activity. On the basis of these results, five marine fungi, Fasciatispora nypae, Caryosporella rhizophorae, Melaspilea mangrovei, Leptosphaeria sp. and ascomycete strain 19 (NF) were selected for further investigation to confirm their biological activity by the disc diffusion assay method. The selected species had various degrees of activity against the test microorganisms, depending on culture conditions (stationary vs. shaking cultures) and incubation time (10-25 days). Only F. nypae showed a wider range of antifungal and antibacterial activity as compared to the remaining fungal strains under investigation. Therefore, bioactivity-guided fractionation was undertaken to isolate the active principles, resulting in the characterisation of 2,2,7-trimethyl-2H-chromen-5-ol (1) which had antimicrobial activity towards test microorganisms. The structure of 1, which previously had only been reported as a synthetic intermediate, but not as a natural product, was elucidated by mass spectrometry in conjunction with one-and two-dimensional NMR spectroscopy.